2015
DOI: 10.1002/14651858.cd008403.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery versus open surgery for the treatment of solid abdominal and thoracic neoplasms in children

Abstract: Minimally invasive surgery versus open surgery for the treatment of solid abdominal and thoracic neoplasms in children (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Only two reviews achieved perfect scores with regards the AMSTAR criteria [122,157]; no articles were considered perfect in relation to their PRISMA score. We, the authors, are no less guilty of failing to report all items on the PRISMA checklist to their entirety in the past [80,173]; with the current study, best attempts were made to follow the checklist.…”
Section: Discussionmentioning
confidence: 99%
“…Only two reviews achieved perfect scores with regards the AMSTAR criteria [122,157]; no articles were considered perfect in relation to their PRISMA score. We, the authors, are no less guilty of failing to report all items on the PRISMA checklist to their entirety in the past [80,173]; with the current study, best attempts were made to follow the checklist.…”
Section: Discussionmentioning
confidence: 99%
“…The only prospective, randomized, controlled study for determining the role of MIS in pediatric cancer failed because of lack of accrual. [35] In their recent Cochrane review, van Dalen et al [10] pointed out that the published reports on solid abdominal and thoracic neoplasms are all case series, retrospective studies, or cohort studies, thus restricting the viability of MIS for pediatric solid tumor and indicating the need for a high-quality randomized, controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…[1,5–9] However, MIS is not generally accepted as an option in such cases, and its use for solid tumors in this population remains limited. [5,10] Therefore, we compared MIS and open surgery for diagnostic exploration and curative resection to determine the safety and feasibility of MIS in pediatric patients with abdominal tumors seen at our center.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown better pulmonary function, earlier return of bowel function and more rapid normalisation of the immune function after MIS. The risk of wound infection is reduced, and a ten-fold decreased risk of incisional hernias has been reported (24,25). The rapid recovery that follows MIS has the additional benefit of an earlier start of chemotherapy and radiotherapy post-operatively, potentially improving the prognosis for patient following MIS (1,20,24,26).…”
Section: Laparoscopic Nephrectomy (Ln)mentioning
confidence: 99%
“…The short-term advantages of a quicker recovery in MIS may be less in children when compared to adults, as children recover faster following an open procedure. Laparoscopy is also associated with lower hospital costs (25,27).…”
Section: Laparoscopic Nephrectomy (Ln)mentioning
confidence: 99%